2023
DOI: 10.3390/polym15163369
|View full text |Cite
|
Sign up to set email alerts
|

Study of Ethylene-Removing Materials Based on Eco-Friendly Composites with Nano-TiO2

Alba Maldonado,
Paulina Cheuquepan,
Sofía Gutiérrez
et al.

Abstract: Ethylene is a phytohormone that is responsible of fruit and vegetable ripening. TiO2 has been studied as a possible solution to slowing down unwanted ripening processes, due to its photocatalytic capacity which enables it to remove ethylene. Thus, the objective of this study was to develop nanocomposites based on two types of eco-friendly materials: Mater-Bi® (MB) and poly(lactic acid) (PLA) combined with nano-TiO2 for ethylene removal and to determine their ethylene-removal capacity. First, a physical–chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The ethylene quantification was conducted in a Perkin Elmer Clarus 580 gas chromatograph (Waltham, MA, USA), with a Head Space Turbo Matrix 40-Perkin Elmer sampler (Waltham, MA, USA) and an RtTM-alumina PLOT column of a 50 m length and 0.53 mm diameter. The gas chromatograph conditions were the same as those used in previous work [ 18 ]. The ethylene removal capacity of different samples was calculated according to Equation (2): where is the ethylene concentration at day 7, and is the ethylene concentration at day 0.…”
Section: Methodsmentioning
confidence: 99%
“…The ethylene quantification was conducted in a Perkin Elmer Clarus 580 gas chromatograph (Waltham, MA, USA), with a Head Space Turbo Matrix 40-Perkin Elmer sampler (Waltham, MA, USA) and an RtTM-alumina PLOT column of a 50 m length and 0.53 mm diameter. The gas chromatograph conditions were the same as those used in previous work [ 18 ]. The ethylene removal capacity of different samples was calculated according to Equation (2): where is the ethylene concentration at day 7, and is the ethylene concentration at day 0.…”
Section: Methodsmentioning
confidence: 99%
“…97,98 Specically, in the food packaging sector, the interaction of TiO 2 NPs with lm matrices enhances mechanical and gas barrier properties, and in some cases, provides a secondary function of ethylene decomposition, contributing to prolonged fruit shelf life aer harvest. [99][100][101] For example, in a study, a chitosan-based lm demonstrated superior strength and enhanced barrier properties by the incorporation of TiO 2 NPs, additionally, it increased the shelf life of tomatoes by delaying ripening. 102 Tian et al (2019) 103 developed a chitosan/TiO 2 coating lm, the resulting lm demonstrated its potential to preserve Gingko biloba seeds by inhibiting mildew, delaying senescence, and preventing declines in rmness.…”
Section: Titanium Dioxide Nanoparticles (Tio 2 Nps)mentioning
confidence: 99%